Does the crowd support innovation? Innovation claims and success on kickstarter - MUKHERJEE, Anirban (Institutional Knowledge at Singapore Management University, 2017)
Online crowdfunding is a popular new tool for raising capital to commercialize product innovation. Product innovation must be both novel and useful (1-4). Therefore, we study the role of novelty and usefulness claims on Kickstarter. Startlingly, we find that a single claim of novelty increases project funding by about 200%, a single claim of usefulness increases project funding by about 1200%, and the co-occurrence of novelty andusefulness claims lowers funding by about 26%. Our findings are encouraging because they suggest the crowd strongly supports novelty and usefulness. However, our findings are disappointing because the premise of crowdfunding is to support projects that are innovative, i.e. that are both novel and useful, rather than projects that are only novel or only useful.